2022
DOI: 10.1126/sciadv.abn9580
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary trade-offs between heat and cold tolerance limit responses to fluctuating climates

Abstract: The evolutionary potential of species to cope with short-term temperature fluctuations during reproduction is critical to predicting responses to future climate change. Despite this, vertebrate research has focused on reproduction under high or low temperatures in relatively stable temperate climates. Here, we characterize the genetic basis of reproductive thermal tolerance to temperature fluctuations in the ostrich, which lives in variable environments in tropical and subtropical Africa. Both heat and cold to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…This suggests that adaptations to favor either cold or heat tolerance in stingless bees are costly, which might limit their potential for adaptation to changes in temperature (e.g. Schou et al, 2022). The two warmadapted species are common in tropical dry forests while the single cold adapted species in our study is among the few stingless bees that are restricted to montane environments in South America.…”
Section: Critical Thermal Limits and Morphological Traitsmentioning
confidence: 82%
“…This suggests that adaptations to favor either cold or heat tolerance in stingless bees are costly, which might limit their potential for adaptation to changes in temperature (e.g. Schou et al, 2022). The two warmadapted species are common in tropical dry forests while the single cold adapted species in our study is among the few stingless bees that are restricted to montane environments in South America.…”
Section: Critical Thermal Limits and Morphological Traitsmentioning
confidence: 82%
“…domesticus , S. c. massaicus, and S. c. australis ) kept at the Oudtshoorn Research Farm (total individuals = 30). We used pedMine version 1.0.0 ( Douglas and Sandefur, 2008 ) to identify the individuals with the most distant links in the population pedigree ( Schou et al, 2022 ), allowing the maximum amount of genetic diversity in populations to be sampled. Samples were sequenced at Science for Life Laboratory, the National Genomics Infrastructure, using Illumina HiSeq 2500, following the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we verified that our analyses of group size effects on individual measures of reproductive success (Specific analyses section ‘Testing how group size and the need for parental care influences male and female reproductive success’) were not influenced by levels of relatedness within groups. Average relatedness between same sex individuals was calculated from a nine-generation pedigree generated from pair breeding adults (see Schou et al, 2022 , for details). Average relatedness was logit transformed prior to analyses due to being bounded between 0 and 1.…”
Section: Supplementary Analysesmentioning
confidence: 99%
“…For instance, elevated CO 2 both raises global temperatures and acidifies the oceans, yet antagonistic selection on physiological responses to warming and acidification prevents simultaneous adaptation to both threats (Dam et al, 2021; see also Kelly et al, 2016). Similarly, a two-decade study of wild ostriches revealed a genetic trade-off between cold-tolerance and heat-tolerance (Schou et al, 2022). As a result, the capacity for adaptation to more variable temperatures under climate change will be precluded because individuals who perform well under the increasingly frequent cold snaps will also perform much worse during the increasingly frequent heat waves, and vice versa.…”
Section: Misalignment Between Genetic Covariation and Direction Of Se...mentioning
confidence: 99%